Analisis Sistem Pembiayaan dan Prosedur Perancangan Akad Pada Perbankan Syariah - Masrofi Bahrul Ulum; Fairuz Sabiq (Jurnal Hukum Ekonomi Syariah, 2026)
This research aims to explain the financing system in Islamic banking and the mechanism for designing financing contracts that comply with the principles of Islamic law. The study emphasizes the importance of accuracy in determining the type of financing contract so that banking institutions can provide professional services while maintaining customer trust through the implementation of transactions that adhere to sharia provisions. The research employs a qualitative approach using a library research method, conducted through the review of various literatures related to financing systems and contracts in Islamic banking. The results of the study indicate that the Islamic financing system generally consists of three main forms: profit-sharing financing, sale-based financing, and lease-based financing. Furthermore, the design of financing contracts in Islamic banking can be carried out through several important stages, including understanding the characteristics of customer needs, assessing the customer’s financial capacity, considering the bank’s sources of third-party funds, and ensuring that the contract complies with the principles of fiqh muamalah (Islamic commercial jurisprudence).Keywords: system, design, sharia financing